2015
DOI: 10.1111/coa.12310
|View full text |Cite
|
Sign up to set email alerts
|

Ivacaftor improves appearance of sinus disease on computerised tomography in cystic fibrosis patients with G551D mutation

Abstract: Patients with CF and G551D mutation, within 6 months of starting ivacaftor had significant improvements in weight, BMI and mean % FEV1. Significant lessening of underlying sinus disease measured by CT scan was noted, suggesting a disease modifying effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 16 publications
2
29
0
1
Order By: Relevance
“…There continues to be concern that these typical endpoints are insensitive to subtle improvements in lung disease in the youngest patients who have minimal detectable lung disease; LCI may be a more sensitive alternative, but is currently not sufficient to support FDA approval [62]. Other novel potential endpoints, such as CT imaging, MRI, hyperpolarized gas and FENO, may prove beneficial in younger CF patients but are not routinely used [70, 71, 85, 86]. Pulmonary exacerbations are not a reliable nor sensitive indicator of improvement in young children with CF given their mild lung disease and rarity of severe exacerbations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There continues to be concern that these typical endpoints are insensitive to subtle improvements in lung disease in the youngest patients who have minimal detectable lung disease; LCI may be a more sensitive alternative, but is currently not sufficient to support FDA approval [62]. Other novel potential endpoints, such as CT imaging, MRI, hyperpolarized gas and FENO, may prove beneficial in younger CF patients but are not routinely used [70, 71, 85, 86]. Pulmonary exacerbations are not a reliable nor sensitive indicator of improvement in young children with CF given their mild lung disease and rarity of severe exacerbations.…”
Section: Discussionmentioning
confidence: 99%
“…In another study from this group, 12 CF patients with a G551D mutation (median age 17 years, mean predicted FEV 1 82.5%) had sinus CT scans performed prior to therapy and after one year of ivacaftor therapy [71]. Sinus CT scans were graded empirically as mild, moderate, or severe; improvement in scoring was noted in all patients (except one who had a normal sinus CT both before and after therapy).…”
Section: Cftr Modulators To Assist Mutant Cftr Functionmentioning
confidence: 99%
“…This study demonstrated the efficacy of ivacaftor in a setting outside of clinical trials but also provided insight into potential mechanistic changes that led to the improvements noted in the clinical trials. A sub-study demonstrated a significant improvement in mucociliary clearance as measured by gamma scintigraphy, which in turn may account for the reported amelioration of CF-related radiological changes in both lung tissue and sinuses [15][16][17]. Intriguingly, the authors also reported a reduction in the proportion of positive cultures for Pseudomonas aeruginosa following institution of ivacaftor therapy, although a substudy examining the respiratory microbiome of 14 participants did not replicate these findings on a molecular level.…”
Section: Cftr Potentiatorsmentioning
confidence: 91%
“…98 Although these clinical trials excluded patients with advanced lung disease (FEV 1 <40% predicted), improvements in FEV 1 (absolute 4-6%), weight gain (2-4 kg), and reduced intravenous antibiotic requirements have been seen in those with advanced disease. [99][100][101] Other beneficial effects reported with ivacaftor in patients with G551D mutations include improvements in exhaled nitric oxide levels 102 ; reduced streptococcus sputum bacterial load 103 ; reduced mucus plugging, bronchiectasis, [104][105][106][107] and sinus disease on computed tomography [108][109][110] ; and positive extrapulmonary effects (improved insulin secretion, 111 112 resolution of cystic fibrosis related diabetes, 113 and reduced hepatic steatosis). 114 In addition to targeting class III gating mutations, ivacaftor has been evaluated in patients over 6 years who have at least one class IV R117H mutation, a mutation associated with residual CFTR function.…”
Section: Late Phase Clinical Trials Of Treatments Targeting the Undermentioning
confidence: 99%
“…There is some evidence to suggest that ivacaftor improves pancreatic endocrine function and sinus disease. [108][109][110][111][112][113] However, it is unclear whether CFTR modulator therapy will permit some chronic maintenance therapies to be safely discontinued to reduce treatment burden, which is currently overwhelming and untenable for many patients. 147 GLOSSARY Adeno-associated vector (AAV): A small virus that infects humans without causing disease.…”
Section: Guidelinesmentioning
confidence: 99%